Pengembangan Model Pembelajaran Savi dalam Meningkatkan Hasil Belajar Siswa Melalui Domain Psikomotorik Siswa di SMAN 9 Kota Jambi - Pratiwi Indah Sari; Ulul Azmi (Jurnal Ilmiah Dikdaya, 2023)
: Teachers as educators have an important role in determining the success of the teaching and learning process. Meanwhile, the learning model serves as a guide for teachers in carrying out the teaching and learning process. In choosing a learning model, it is determined by the level of student ability, the material to be taught, and also the goals to be achieved. In addition, each learning model has stages that students must know from the guidance provided by the teacher. The use of learning models that are appropriate to the situation and conditions will certainly have an impact on the sustainability of teaching and learning activities in the classroom. Based on the description of the previous data analysis table, both the control and experimental classes showed a fairly good increase. However, the average score is still far from the expectations and desired achievements. Thus, in teaching and learning activities that are carried out, it is very necessary to have a comprehensive planning and process for various factors and possibilities that can hinder or support the achievement of better learning in the future. Thus, it can be explained that gaps in learning can occur due to the conditions and timing of activities that have not been able to be optimized properly. Students are not only the cause but also the impact on the success of a teacher in carrying out teaching and learning activities. Therefore, encouraging students to study harder and harder can be appreciated through academic and intellectual activities and interactions, not only limited to the school's vision, mission, and goals